The effect of proprioceptive neuromuscular facilitation and static stretch training on running mechanics - Caplan, N.; Rogers, R.; Parr, M. K.; Hayes, P. R. (The Journal of Strength and Conditioning Research, 2009)
There is a long-standing belief that increased range of movement (RoM) at the hip or knee will improve running mechanics; however, few studies have examined the effect of such an increase in RoM. The aim of this study was to determine the influence of 2 methods of stretch training (static and proprioceptive neuromuscular facilitation [PNF]) on high-velocity running. Eighteen rugby league players were assessed for maximum sprinting velocity. They were randomly allocated into 2 stretch training groups: PNF or static. Each group trained their hamstrings 4 d/w for 5 weeks. Pre- and posttraining subjects were videoed while running at 80% of maximum velocity. The video was digitized to identify biomechanical changes in hip flexion (HF), knee extension (KE), stride length (SL), stride rate (SR), and contact time (tc). Stretch training resulted in gains (p < 0.05) in HF for the static stretch (SS) (4.9%) and PNF (7.6%) groups. There were reductions in KE (p < 0.05) for SS (1.0%) and PNF (1.6%) groups. Stride mechanics were also altered after training. There were increases in SL (p < 0.05) for SS (7.1%) and PNF (9.1%) and a concomitant reduction in SR (p < 0.05) for SS (1.9%) and PNF (4.3%). No changes were observed in tc in either group. In conclusion, both SS and PNF training improved HF RoM and running mechanics during high-velocity running. These findings suggest that stretch training undertaken at the end of regular training is effective in changing running mechanics.